Adenocarcinoma of the Lung in down Syndrome: First Clinical Report. Issue 4 (July 2013) - Satgé, Daniel; Salmeron, Sergio; Homsi, Toufik; Réthoré, Marie-Odile; Tredaniel, Jean
Lung cancer is rare in persons with Down syndrome, and the clinical presentation of the disease has not been described in adults with intellectual disability. We report the first detailed clinical observation of a 33-year-old man with Down syndrome who developed an adenocarcinoma of the lung 30 years after an acute lymphoblastic leukemia in infancy. Despite advanced disease at initial presentation and extensive tumor spreading during the course of the disease, he presented with unusually mild symptoms. The scarcity of lung cancer in people with intellectual disability, and particularly those with Down syndrome, is due, in part, to reduced tobacco use. However, cytogenetic and molecular studies suggest that genes mapping to chromosome 21 may protect against lung cancer. Numerous reports also suggest that, in persons with Down syndrome and other intellectual disability, cancers are often discovered late, leading to loss of the chance of cure and recovery.